LEADERSHIP IN HIGHER EDUCATION: A Phenomenological Study on Developing Successful Academic Leadership in Universities in Cambodia - Vannak, Hour; Kreng, Dr. Heng (Srawung: Journal of Social Sciences and Humanities, 2025)
Higher education plays a pivotal role in national development, particularly in rapidly evolving societies like Cambodia. In Cambodia, where the higher education landscape is undergoing rapid transformation and expansion, understanding and developing effective academic leadership is particularly crucial. Strong academic leadership is essential for navigating the complex challenges facing higher education today, including globalization, technological advancements, evolving student demographics, and increasing demands for accountability and quality assurance. Despite the acknowledged importance of academic leadership in higher education, there is a limited understanding of the specific experiences and factors that contribute to successful academic leadership within the unique context of Cambodian universities. A phenomenological study was employed for interviewing and collecting the insights from 12 academic participants in universities. This study examines the experiences and challenges faced by university leaders in Cambodia, as well as the key factors contributing to their success. Drawing on data analysis of career paths and leadership development. The research reveals that Cambodian university leaders bring diverse prior experiences to their roles, including teaching, administration, research, and non-academic work, which provide valuable skills and perspectives. However, they also encounter significant challenges stemming from limited funding, faculty development needs, technological gaps, cultural expectations, and infrastructural limitations. Despite these obstacles, successful university leaders demonstrate visionary thinking, emotional intelligence, ethical decision-making, collaborative approaches, adaptability, and a commitment to innovation and transparency. These findings highlight the complex landscape of higher education leadership in Cambodia and offer insights into the qualities and strategies necessary for effective leadership in this context.